Mechanical characterization of natural fiber reinforced polymer composites and their application in Prosthesis: A review. (2022) - Malalli, Chandrashekhar S.; Ramji, B.R.
Graphical abstract: Abstract: Natural fiber-reinforced polymer composites (NFRP) as eco-friendly and sustainable materials were receiving attention from researchers because their manufacturing and disposal have a small load on the environment other than the synthetic polymer composites. These composites are potentially used in medical devices and various engineering applications, due to some unique characteristics, such as biocompatibility, high specific strength, low thermal conductivity, and Biodegradability. The aim of the paper is to examine the latest technology in the research and development of NFRP. This review article emphasizes research effort on fabrication of NFRP and its material properties like tensile strength, flexural strength, impact strength, biodegradability, and biocompatibility. And also reports that natural fiber PALF-Sisal reinforced polymer composites have better mechanical performance in the application of prosthesis than synthetic fiber reinforced polymers.